2012
DOI: 10.2174/1874473711205020117
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Alcohol Use and Sexual Risk Behaviors Among African American Women Across Three Developmental Periods: A Review

Abstract: Background: African American women experience increased rates of sexually transmitted diseases and HIV. The use of alcohol may increase sexual risk behaviors among this population. Purpose: This paper provides a review and critique of the literature examining the association between alcohol use and sexual risk behaviors among African American females including a: (a) synthesis of research findings from adolescent, college-aged/early adulthood, and adult samples; (b) methodological critique of the literature;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 46 publications
(118 reference statements)
4
39
0
Order By: Relevance
“…The SRAEs of African American women attending an STI clinic may result in high risk sex and also in unwanted/forced/coerced sex, and suggests the importance of developing integrated alcohol -sexual risk reduction interventions for high risk women (Sales et al, 2012; Stappenbeck et al, 2013). First, we recommend that such interventions increase self-awareness and self-monitoring by helping women identify their SRAEs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The SRAEs of African American women attending an STI clinic may result in high risk sex and also in unwanted/forced/coerced sex, and suggests the importance of developing integrated alcohol -sexual risk reduction interventions for high risk women (Sales et al, 2012; Stappenbeck et al, 2013). First, we recommend that such interventions increase self-awareness and self-monitoring by helping women identify their SRAEs.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol use, particularly binge drinking ≥4 drinks/occasion for women (Wechsler, Dowdall, Davenport, & Rimm, 1995) is correlated with HIV/STI risk behaviors which include: unprotected vaginal and anal sex, multiple sex partners, coerced or forced sex, and sex with high- risk partners (Cooper, 2002; Hutton et al, 2008; Jenness, Beier, Neaigus, Murrrill, Wendel, & Hagan, 2011; Rehm, Shield, Joharchi, & Shuper, 2012; Scott-Sheldon, Senn, Carey, Urban, & Carey, 2013; Seth et al, 2011; Stockman, Campbell, & Celentano, 2010). Among African American women, even non-abuse levels of consumption are associated with HIV/STI risk behaviors and STIs (Sales, Brown, Vissman, & DiClemente, 2012; Seth et al, 2011). While African American women have lower prevalence rates of alcohol use and binge drinking than white or Hispanic women, they experience more adverse medical and social outcomes from their alcohol use (Boyd, Mackey, & Phillips, 2006; Caetano, Schafer, & Cunradi, 2001; Mulia, Ye, Greenfield, Zemore, 2009; Sales et al, 2012; Sempos, Rehm, Wu, Crespo, & Trevisan, 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that alcohol consumption is the key driver of HIV/AIDS in Africa, especially through risk behaviours such multiple sex partnerships and inconsistent condom use (Leclerc-Madlala, 2009;Morojele, 2013;Braithwaite et al, 2014). Moreover, recent systematic reviews and meta-analyses have shown that alcohol use was found to be associated with HIV risk behaviours especially having multiple sex partners (Scott et al, 2013;Sales et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…41,42 Samples consisting solely of African American participants indicate associations between alcohol and sexual risk intentions or behaviors. 2,43,44 A smaller body of research has examined race and ethnicity as moderators of the links between alcohol use and sexual behavior, often finding stronger associations between alcohol consumption and sexual behavior among whites. [45][46][47][48] While alcohol consumption increases the likelihood of sexual activity across relationship types, this effect seems to be strongest for sex with casual partners, 10,16,46,[49][50][51][52][53][54] likely owing to the centrality of alcohol consumption in scripts that guide casual sex encounters.…”
Section: Introductionmentioning
confidence: 99%